WRAN and LTE comparison in rural environments (2012)
Digital Dividend refers to frequency bands that currently are being occupied by conventional analog television that will be free after the analogue switch off and digital TV deployment. This paper discusses the importance of the 700 MHz band to achieve coverage goals and enhance rural development and economy by increasing levels of broadband Internet access. We performed a technical comparison of two technologies: LTE as a commercial positioned standard, and 802.22 as a new proposed and interesting. Simulation results are obtained operating in the 700 MHz band in rural areas, and finally there are conclusions.